2021
DOI: 10.1542/hpeds.2020-003509
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Monitor Alarm Burden and Nurses’ Subjective Workload in a Children’s Hospital

Abstract: BACKGROUND AND OBJECTIVES: Physiologic monitor alarms occur at high rates in children's hospitals; #1% are actionable. The burden of alarms has implications for patient safety and is challenging to measure directly. Nurse workload, measured by using a version of the National Aeronautics and Space Administration Task Load Index (NASA-TLX) validated among nurses, is a useful indicator of work burden that has been associated with patient outcomes. A recent study revealed that 5-point increases in the NASA-TLX sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Pumps are major sources of alarms in the NICU. An increase in non-urgent or unidentifiable alarms can interrupt nurses’ workflow, increasing the risk of missed care [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pumps are major sources of alarms in the NICU. An increase in non-urgent or unidentifiable alarms can interrupt nurses’ workflow, increasing the risk of missed care [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior work conducted by our lab has demonstrated that when nurses experience more than 40 alarms within a 2-hour period, their measured subjective workload increases to a degree associated with missing important tasks, threatening the quality and safety of the care they deliver. 12,17 Given that nurses care for multiple patients, it is likely that the excess alarms introduced by guideline-discordant continuous monitoring contribute to increased nurse workload and alarm fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Frequent alarms are associated with slower nurse response times 10,11 and increased nurse subjective workload. 12 The rate of excess alarms occurring during guideline-discordant, continuously SpO 2 monitored time, compared to the rate of alarms occurring during guideline-concordant (intermittently measured SpO 2 ) time, has not been evaluated. The magnitude of this difference in alarm rates, if such a difference exists, will inform prioritization of guideline-discordant continuous SpO 2 measurement de-implementation.…”
mentioning
confidence: 99%
“…This involves manual titration of fluid and vasopressor infusions for the treatment of a patient with severe shock, which can be a time consuming process [1]. Also, the excessive cognitive load associated with these tasks, amplified across an ICU with numerous critically ill patients, can lead to errors, burnout, job dissatisfaction, and increased patient mortality [2][3][4].…”
Section: Introductionmentioning
confidence: 99%